Fabrication and Optimization of Primary Batteries Using Ni/Graphene Nanosheet Electrodes - Tarigan, Kerista; Siburian, Rikson; Sitorus, Erika Arta Mevia; Purba, Frikson Jony; Manik, Yosia Gopas Oetama (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
This study aims to investigate the impact of varying the mass ratio of Ni to Graphene Nano Sheets (GNS) and how incorporating GNS affects the performance of a primary battery prototype (Ni/GNS//electrolyte//GNS). The primary battery prototype was developed using both impregnation and alloy methods. Different mass ratios of Ni/GNS to electrolyte to GNS were tested, including ratios of 1:2:1 (A), 2:2:1 (B), 1:2:2 (C), 2:1:2 (D), and 1:1:2 (E). The characterization of GNS, Ni/GNS, and the primary battery prototype involved using X-Ray Diffraction (XRD) and Scanning Electron Microscope-Energy Dispersive X-Ray (SEM-EDX) instruments. A multimeter was employed to measure electrical conductivity, energy density, and power density. A potentiostat/galvanostat was used to measure cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). XRD analysis showed a broad and weak peak at 2θ= 24.32° for GNS, confirming its successful synthesis. Additionally, a peak at 2θ = 43.5° indicated effective deposition of Ni on the GNS surface in Ni/GNS. The SEM-EDX results supported the XRD findings, showing regularly spaced pores and a thin surface layer in GNS. Notably, white spots on the graphene surface in Ni/GNS indicated successful Ni deposition. In terms of electrical conductivity, the highest value was observed in the primary battery prototype for sample D (2:1:2), which measured 1.11 S/cm2. These results were also supported by measurements of energy density and power density in sample D, which achieved the highest values among all samples, with 144,788 Wh/kg and 252,500 W/kg, respectively. Moreover, the CV and EIS measurements remained stable at 0.30 kΩ and 0.88 kΩ, suggesting that GNS could potentially conduct electrons owing to its electrical conductivity.